2011
DOI: 10.1186/1550-2783-8-16
|View full text |Cite
|
Sign up to set email alerts
|

The effects of IQPLUS Focus on cognitive function, mood and endocrine response before and following acute exercise

Abstract: BackgroundPhosphatidylserine (PS) is a phospholipid found in cell membranes of most animals and plants. PS has been shown to reduce stress and increase performance in runners, cyclists and golfers. The purpose of this study was to investigate the effects of a PS containing formulation on cognitive function, mood and endocrine response before and after intense resistance exercise.Methods18 lower body, resistance trained, college aged males ingested 14 days of supplement (IQPLUS Focus, providing 400 mg of soy-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 14 publications
2
23
1
Order By: Relevance
“…However, the dosage in that study was significantly greater than the present study (500 mg/kg bodyweight). Further evidence of the anti-hyperglycemic effects of RT has been provided by Pischel et al [29]. Using the same aqueous extract of RT and dosage used in the current study, Pischel et al [29] reported lower blood glucose levels in both animals and humans (albeit non-statistically) following ingestion.…”
Section: Discussionsupporting
confidence: 61%
“…However, the dosage in that study was significantly greater than the present study (500 mg/kg bodyweight). Further evidence of the anti-hyperglycemic effects of RT has been provided by Pischel et al [29]. Using the same aqueous extract of RT and dosage used in the current study, Pischel et al [29] reported lower blood glucose levels in both animals and humans (albeit non-statistically) following ingestion.…”
Section: Discussionsupporting
confidence: 61%
“…Monteleone et al (30) also found that supplementing with 400 mg/d of PS for 10 days did not affect cortisol levels. Based on the findings of Monteleone et al (30) and Parker et al (33), 400 mg/d of PS supplemented for 10-14 days may be inadequate to blunt the rise in cortisol from exercise. It may be necessary to either use higher dosages (i.e., 800 mg/d of PS) or to load for longer durations (i.e., .14 days) to receive benefits from PS in regards to the blunting of cortisol induced by exercise.…”
Section: Soybean Phosphatidylserine and Exercisementioning
confidence: 99%
“…Parker et al (33) examined the effects of 400 mg/d of S-PS supplemented over 14 days on 18 lower-body resistance-trained males using a randomized, doubleblind, placebo-controlled, crossover design without a washout period. The investigators measured cognitive performance, mood, and endocrine response (cortisol and testosterone) before and after a lower-body resistance training session involving 5 sets of 10 repetitions at 70% of their 1 repetition maximum using the squat, leg press, and leg extension exercise (the researchers noted an 87% increase in plasma cortisol during pilot work for the study).…”
Section: Soybean Phosphatidylserine and Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Schubert, Contreras, Franz, and Hellhammer [18] reported improved visuospatial memory in a post-hoc split of high stress load older adults after intake of a similar PL drink. Furthermore, supplementation with S-PS has been shown to 4 improve serial subtraction test accuracy and completion time in young males [19]. However, these effects were independent of cortisol or subjective stress response.…”
mentioning
confidence: 96%